2018
DOI: 10.1186/s40104-018-0302-9
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated conceptus signaling does not favor establishment of pregnancy in beef cattle

Abstract: BackgroundInsufficient production of anti-luteolytic signals by the pre-attachment embryo is considered a major cause of pregnancy failure in cattle. We tested the hypothesis that transfer of multiple blastocysts (n = 5/recipient) and progesterone (P4) supplementation amplify anti-luteolytic signaling and reduce embryonic losses in beef cattle. Cows detected in estrus (D0; n = 104) were assigned randomly to receive 150 mg of injectable long-acting P4 (iP4) or vehicle (non-iP4) on D4 and transcervical transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
1
Order By: Relevance
“…In the initial development of Bali cattle embryos cultured for 48 h, there were 2-, 4-, 8 and 16-cell cleavage and 42% of which developed from 542 oocytes. The development of Bali cattle embryos cultured in vitro is different from that reported by Martins et al (2018) who stated that the stage of cattle embryo cell development on the second day only reaches 4-cell division. Marsico et al (2019) stated that the initial stage of embryonic development is difficult to be carried out because they involve processes that are molecularly dynamically arranged and undergo complex structural changes.…”
Section: Discussioncontrasting
confidence: 84%
“…In the initial development of Bali cattle embryos cultured for 48 h, there were 2-, 4-, 8 and 16-cell cleavage and 42% of which developed from 542 oocytes. The development of Bali cattle embryos cultured in vitro is different from that reported by Martins et al (2018) who stated that the stage of cattle embryo cell development on the second day only reaches 4-cell division. Marsico et al (2019) stated that the initial stage of embryonic development is difficult to be carried out because they involve processes that are molecularly dynamically arranged and undergo complex structural changes.…”
Section: Discussioncontrasting
confidence: 84%
“…Other experiments in which embryos were repeatedly transferred to cows have revealed that there are subpopulations of highly fertile females that become pregnant after all, or nearly all, ET and other subpopulations that rarely or never become pregnant ( McMillan and Donnison, 1999 ; Geary et al, 2016 ; Moraes et al, 2018 ). Further evidence for poor uterine receptivity as a cause of infertility was the finding that 14 of 37 (32.4%) recipients receiving five embryos failed to become pregnant to any embryo ( Martins et al, 2018a ). Examples of cow factors associated with poor P/ET are low body condition score ( Mapletoft et al, 1986 ; Wallace et al 2011 ), poor weight gain ( Fernandes et al, 2016 ), lactation or parity in dairy cattle ( Dochi et al, 1998 ; Hasler, 2001 ; Ferraz et al, 2016 ), temperament ( Kasimanickam et al, 2018 , 2019 ), and periparturient or postpartum disease ( Ferraz et al, 2016 ; Ribeiro et al, 2016 ; Barbosa et al, 2018 ; Estrada-Cortés et al, 2019 ).…”
Section: Causes Of Pregnancy Loss Associated With Etmentioning
confidence: 99%
“…Under the influence of thermal stress, the duration and intensity of estrus are reduced, with a clear decrease in activity and other manifestations such as the acceptance of copulations [15]. It should, moreover, be noted that the higher incidence of anestrus and silent heats are one of the most common observations in cows exposed to high temperatures [16]. In the Azores as in the interior of the island the pastures are abundant from the end of May to the beginning of July, deliveries occur mostly in this period occurring the mating in September and October, at which point the pasture still has enough fodder to trigger estrus behavior in females.…”
Section: Resultsmentioning
confidence: 99%
“…Açores" Cattle, the weaned calf is the main source of revenue. Table 1 shows the parameters key to assess reproductive performance [16]. Reproductive efficiency has long been recognized as one of the most important aspects of a bovine holding regardless of type.…”
Section: Resultsmentioning
confidence: 99%